Effect of Mechanical Analysis of Magnesium AZ 80 Alloy and Aluminium 7075 Alloy Using Diffusion Bonding - Renjith Nimal, R.J. Golden; Sivakumar, M.; Esakkimuthu, G. (International Journal of Psychosocial Rehabilitation, 2019)
The principal problem when joining magnesium alloy (Mg) and aluminium alloy (Al) lies within the existence of formation of oxide films and brittle intermetallic within the bond region. But diffusion welding is accustomed be part of these alloys while not a lot of problem. In this investigation, an attempt was made to analyse the mechanical properties such as lap shear strength, Ram tensile strength and microhardness for diffusion bonding of AZ80 magnesium (Mg) and AA7075 aluminium (Al) dissimilar materials. The bonding quality of the joints was checked by microstructure analysis. This work is conducted to obtain better understanding and characterization of the diffusion bonding of similar and dissimilar metals. It also aimed to obtain optimum parameters for diffusion bonding of aluminium coating over magnesium alloy with Aluminium alloy. This work is conducted to obtain better understanding and characterization of the diffusion bonding of similar and dissimilar metals. It also aimed to obtain optimum parameters for diffusion bonding of aluminum coating over magnesium alloy with aluminum alloy. These two metals are jointed inside the die after finishing surface treatment